Cell Physiol Biochem 2020
DOI: 10.33594/000000271
|View full text |Cite
|
Sign up to set email alerts
|

Glycolaldehyde-Derived High-Molecular-Weight Advanced Glycation End-Products Induce Cardiac Dysfunction through Structural and Functional Remodeling of Cardiomyocytes

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Indeed, the activation of RAGEs stimulates the signaling of nuclear factor kappa B (NF-κB)-dependent proinflammatory mediators including tumor necrosis factor alpha (TNF-α), interleukin (IL)-1, IL-6, and RAGE itself, initiating a vicious cycle [ 55 ]. What is more, the injection of high-molecular-weight (HMW-)AGEs induces cardiac dysfunction in vivo [ 56 ]. The hearts of the rats treated with HMW-AGEs were characterized by elevated mass as well as decreased contractility [ 56 ].…”
Section: Diabetic Cardiomyopathy (Dcm)mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the activation of RAGEs stimulates the signaling of nuclear factor kappa B (NF-κB)-dependent proinflammatory mediators including tumor necrosis factor alpha (TNF-α), interleukin (IL)-1, IL-6, and RAGE itself, initiating a vicious cycle [ 55 ]. What is more, the injection of high-molecular-weight (HMW-)AGEs induces cardiac dysfunction in vivo [ 56 ]. The hearts of the rats treated with HMW-AGEs were characterized by elevated mass as well as decreased contractility [ 56 ].…”
Section: Diabetic Cardiomyopathy (Dcm)mentioning
confidence: 99%
“…What is more, the injection of high-molecular-weight (HMW-)AGEs induces cardiac dysfunction in vivo [ 56 ]. The hearts of the rats treated with HMW-AGEs were characterized by elevated mass as well as decreased contractility [ 56 ]. The microscope analysis revealed cardiomyocytes’ concentric hypertrophy, whereas ultrastructural examination has shown disrupted cellular architecture, decreased mitochondrial density, and functionality [ 56 ].…”
Section: Diabetic Cardiomyopathy (Dcm)mentioning
confidence: 99%
See 1 more Smart Citation
“…and euthanized by injection with an overdose of sodium pentobarbital (Dolethal, Vetoquinol, 200 mg/kg, i.p.). Hearts were harvested and single cardiomyocytes were isolated from the LV by enzymatic dissociation through retrograde perfusion of the aorta, as described previously [58,59]. The hearts were perfused for 1 min with a normal Tyrode solution and then connected to a Langendorff perfusion system for following perfusion steps at 37 • C and 100% O 2 oxygenation.…”
Section: Cardiomyocyte Isolation and Unloaded Cell Shorteningmentioning
confidence: 99%
“…In this context, our research group previously showed that a chronic increase in HMW-AGE levels in vivo leads to cardiac dysfunction in rats, characterised by interstitial fibrosis, myocardial wall hypertrophy, and increased left ventricular pressure [ 23 ]. At the cellular level, chronic exposure to high levels of HMW-AGEs induces cardiomyocyte remodelling, resulting in impaired cellular function [ 24 ]. In addition, we have previously shown that the chronic administration of HMW-AGEs disturbs the vasomotor balance in rat aortae which is the result of increased oxidative stress [ 25 ].…”
Section: Introductionmentioning
confidence: 99%